Synergistic relationship of bacterial blight and anthracnose disease pathogen in cassava multiple infection - Fokunang, C.N.; Dixon, Alfred G.O.; Ikotun, T. (Science Alert, 2003)
A study was conducted at the greenhouse of the international institute of Tropical Agriculture, Ibadan,Nigeria to investigate the synergistic relationship of xanthomonas campestris pv. Manihotics (causal agent of cassava bacteria blight CBB), and colletotrichum gloeosporiodes f.sp manihotics (causal agent of cassava anthracnose disease CAD), in cassava multiple infection. There were statistical differences(p<0.05) in the cassava genotype following sequential inoculation of the pathogens and single pathogen inoculation alone